Kewajaran Pengalokasian Anggaran Berbasis Analisis Standar Belanja (ASB) pada Pemerintah Kota Padang - Putri Intan Permata Sari; Dodi Suryadi (SAFE-Network, 2024)
This research aims to analyze the fairness of expenditure in Coordination activities and Preparation of Performance Achievement Reports and Overview of SKPD Performance Realization using the Standard Expenditure Analysis (ASB) method in the Padang City Government for Fiscal Year 2022. Of the 43 SKPDs in the Padang City Government, only 19 SKPDs are can continue to be researched. The stages of preparing the ASB are by inputting data and grouping similar data, determining cost drivers, creating a regression equation, determining the average, upper limit and lower limit, and analyzing the reasonableness of the costs of the ASB model that has been prepared. As for the preparation of the ASB model using SPSS with the regression equation obtained is Y = Rp 7,116,556+86,035X, where Based on this equation, there are 5 underfinancing SKPDs, 6 overfinancing SKPDs, and 8 SKPDs that get fair value.